ANALISIS EFISIENSI PEMASARAN UDANG WINDU (Penaeus monodon) DI DESA SUNGAI LUMPUR KECAMATAN CENGAL KABUPATEN OGAN KOMERING ILIR - Riandi, Riandi; Batubara, Mustopa Marli; Iskandar, Sutarmo (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
ABSTRACTThis study aims to find out the marketing channel of tiger shrimp from the farmers to the final consumer and efficient marketing of tiger shrimp in Sungai Lumpur village Regency Cengal District Ogan Komering Ilir. This research was conducted in Sungai Lumpur village Regency cengal District Ogan Komering Ilir from May-Juli 2017. The method used in this research is survey method, for sampling method used simple random sampling method. To collect the data in this research used observation and interview methods by using a quisionary aids that have been prepared previously. Data processing is done using kualitatif and kuantitatif analysis. The result of this research indicates there are three marketing channels of tiger shrimp in Sungai Lumpur village Regency Cengal District Ogan Komering Ilir and the three marketing channels are efficient.